Standardisation and language criticism in English - Busse, Beatrix; Möhlig-Falke, Ruth; Vit, Bryan (Handbuch europäische Sprachkritik online, 2018)
In negotiations of what a standard language is or should be, language criticism - with its evaluation of language and its speakers - has a central role. The article gives an overview of how the attitudes towards standard written as well as spoken British English have developed and changed over time and in the various socio-historical contexts. From a diachronic perspective, a tendency can be observed which begins with an orientation towards the linguistic variety used by the sophisticated elite in the middle of the 18th century and gradually moves towards acceptance and appreciation of local dialects and new standard varieties other than British English in the 20th century. For a long time, however, the ability to use ‘correct’, i. e. standard language, has been associated with education, appropriate social behaviour and decorum. This view is still subliminally present in British English and other national varieties, such as American English, today. Standardisation also plays a role in the public debates about the politically correct use of certain forms of language as well as in academic discussions about the influence that linguistic discourse exerts upon the attitudes formed about certain social groups.
Gesehen am 23.05.2023